Legal Protection For Consumers In Digital Transactions: Case Study And Analysis - Sri Anggraini Kusuma Dewi (Journal of International Multidisciplinary Research, 2025)
This study aims to analyze the effectiveness of legal protection for consumers in digital transactions in Indonesia. The method used is library research with a normative juridical approach. The results of the study indicate that Indonesia actually has an adequate legal basis to protect digital consumers, which is primarily sourced from Law Number 8 of 1999 concerning Consumer Protection and Law Number 19 of 2016 concerning Information and Electronic Transactions. These regulations have set out basic principles such as the obligation of business actors to provide honest information, consumer rights to security, and the recognition of electronic evidence. However, its implementation in the field encounters various significant obstacles. Case studies on e-commerce and fintech platforms reveal that consumer losses still often occur, such as products that do not match the description, difficulties with refunds, and the vulnerability of personal data. The key finding of this study is that the main challenge lies not in the legal vacuum, but in three aspects: (1) low digital literacy and consumer law so that they are not optimal in fighting for their rights; (2) alternative dispute resolution mechanisms such as BPSK and ODR (Online Dispute Resolution) which are not yet effective, fast, and easily accessible; and (3) weak supervision and law enforcement against unscrupulous business actors in the digital space. Therefore, it is concluded that digital consumer protection efforts require a holistic approach that relies not only on regulations, but also through massive public education, strengthening dispute resolution institutions, and closer synergy between the government, business actors, and the community.